2010
DOI: 10.3842/sigma.2010.099
|View full text |Cite
|
Sign up to set email alerts
|

Notes on TQFT Wire Models and Coherence Equations for SU(3) Triangular Cells

Abstract: Abstract. After a summary of the TQFT wire model formalism we bridge the gap from Kuperberg equations for SU (3) spiders to Ocneanu coherence equations for systems of triangular cells on fusion graphs that describe modules associated with the fusion category of SU (3) at level k. We show how to solve these equations in a number of examples.Key words: quantum symmetries; module-categories; conformal field theories; 6j symbols 2010 Mathematics Subject Classification: 81R50; 81R10; 20C08; 18D10 ForewordStarting w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(43 citation statements)
references
References 35 publications
(121 reference statements)
1
42
0
Order By: Relevance
“…At this place we just illustrate on one example the importance of the faithfulness requirement: the group Σ 168 × Z 3 has 18 irreps, six of them, actually three pairs of complex conjugates, labelled 4, 5, 6, 7, 8, 9 are of dimension 3, but the irreps of the pair (4, 5) are not faithful whereas the two pairs (6, 7) and (8,9) are. As it happens the fusion graphs associated with the faithful representations (namely those labeled 6,7,8,9,11,12,14,15,17,18) are connected; this is not so for the others, in particular for the 3-dimensional irreps labelled 4 and 5. So the natural (or embedding) irreps, with respect to SU(3), are 6, 7, 8, 9 and we may choose to draw the fusion graph of N 6 for instance (see Fig.…”
Section: Additional Remarksmentioning
confidence: 99%
See 4 more Smart Citations
“…At this place we just illustrate on one example the importance of the faithfulness requirement: the group Σ 168 × Z 3 has 18 irreps, six of them, actually three pairs of complex conjugates, labelled 4, 5, 6, 7, 8, 9 are of dimension 3, but the irreps of the pair (4, 5) are not faithful whereas the two pairs (6, 7) and (8,9) are. As it happens the fusion graphs associated with the faithful representations (namely those labeled 6,7,8,9,11,12,14,15,17,18) are connected; this is not so for the others, in particular for the 3-dimensional irreps labelled 4 and 5. So the natural (or embedding) irreps, with respect to SU(3), are 6, 7, 8, 9 and we may choose to draw the fusion graph of N 6 for instance (see Fig.…”
Section: Additional Remarksmentioning
confidence: 99%
“…To probe equation (7), we have to look at groups possessing complex representations. In the case of SU(2) subgroups, equation (7) holds, and this was easy to check since only the cyclic and binary tetrahedral subgroups have complex representations. It was then natural to look at subgroups of SU(3) and we found that (7) holds true for most subgroups of SU(3) but fails for some subgroups like F = Σ 72×3 or L = Σ 360×3 .…”
Section: Sum Rules For the S Matrixmentioning
confidence: 99%
See 3 more Smart Citations